Kepadatan Nerita sp Di Perairan Pantai Negeri Suli Teluk Baguala Kabupaten Maluku Tengah - Liline, Sintje; Kubangun, Muhammad Tarmizi; Kurnia, Tri Santi; Jainudin Heremba, Wa Nurul Mutmainah (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
Suli in Baguala Bay, Central Maluku Regency has waters with various types of substrates, namely sandy, muddy and rocky which are rich in benthic organisms. One of them is the gastropod type Nerita sp which is widely used by the population for food needs. The existence of gastropods, especially Nerita sp needs to be maintained and preserved so that the diversity and density of Nerita sp can be maintained and well maintained. This study aims to determine the type and density of Nerita sp. In the coastal waters of Suli, Baguala Bay, Central Maluku district. This research is a descriptive study, namely research to reveal information about the density of Nerita sp in the coastal waters of Suli Baguala Bay, Central Maluku district which is presented in the form of tables and numbers and the research was conducted in July 2019. Based on the description of the morphology of Nerita sp. from the land of Suli, including the species Nerita chamaeleon. The total number of Nerita chamaeleon found was 566 individuals with a density value of 11.32 and categorized as having sufficient density. It is necessary to do further research on the nutritional content and its use by the people of Suli. Keywords: Density, Nerita sp, Suli